A systematic study and literature review of parental somatic mosaicism of FBN1 pathogenic variants in Marfan syndrome. Issue 6 (28th April 2021) - Fernández-Álvarez, Paula; Codina-Sola, Marta; Valenzuela, Irene; Teixidó-Turá, Gisela; Cueto-González, Anna; Paramonov, Ida; Antolín, María; López-Grondona, Fermina; Vendrell, Teresa; Evangelista, Artur; García-Arumí, Elena; Tizzano, Eduardo F
Abstract : Background: A proportion of de novo variants in patients affected by genetic disorders, particularly those with autosomal dominant (AD) inheritance, could be the consequence of somatic mosaicism in one of the progenitors. There is growing evidence that germline and somatic mosaicism are more common and play a greater role in genetic disorders than previously acknowledged. In Marfan syndrome (MFS), caused by pathogenic variants in the fibrillin-1 gene ( FBN1 ) gene, approximately 25% of the disease-causing variants are reported as de novo. Only a few cases of parental mosaicism have been reported in MFS. Methods: Employing an amplicon-based deep sequencing (ADS) method, we carried out a systematic analysis of 60 parents of 30 FBN1 positive, consecutive patients with MFS with an apparently de novo pathogenic variant. Results: Out of the 60 parents studied (30 families), the majority (n=51, 85%) had a systemic score of 0, seven had a score of 1 and two a score of 2, all due to minor criteria common in the normal population. We detected two families with somatic mosaicism in one of the progenitors, with a rate of 6.6% (2/30) of apparently de novo cases. Conclusions: The search for parental somatic mosaicism should be routinely implemented in de novo cases of MFS, to offer appropriate genetic and reproductive counselling as well as to reveal masked, isolated clinical signs of MFS in progenitors that may require specific follow-up.